Geospatial Analysis for Flood Hazard Zonation in District Muzaffargarh (Pakistan) (Journal of Asian Development Studies, 2025)
Flash floods pose a significant hazard to communities worldwide, underscoring the need for effective risk assessment strategies to mitigate their impact. This study applies a Flood Risk (FR) model to evaluate flash flood vulnerability in the Muzaffargarh District of Punjab, Pakistan. Six key conditioning factors—elevation, slope, aspect, curvature, land use/land cover, and rainfall— were integrated within a geospatial framework to identify and map flood-prone areas. The analysis categorised the region into five vulnerability zones: very high (36%), high (24%), moderate (16%), low (12%) and very low (11%). Notably, the high-to-very high-vulnerability zones are predominantly concentrated in the eastern, western, and southern portions of the district. The model's accuracy was validated through historical flood records and spatial overlay techniques, confirming its reliability. This geospatial approach offers a cost-effective and scalable solution for rapid flood risk assessment in data-scarce regions. The findings serve as a vital tool for integrating disaster risk reduction into regional planning and climate adaptation strategies.